Building C(sp3) Molecular Complexity on 2, 2′‐Bipyridine and 1, 10‐Phenanthroline in Rhenium Tricarbonyl Complexes. Issue 1 (23rd November 2020) - Arevalo, Rebeca; López, Ramón; Falvello, Larry R.; Riera, Lucía; Perez, Julio
Abstract: The reactions of [Re(N‐N)(CO)3 (PMe3 )]OTf (N‐N=2, 2′‐bipyridine, bipy; 1, 10‐phenanthroline, phen) compounds with t BuLi and with LiHBEt3 have been explored. Addition to the N‐N chelate took place with different site‐selectivity depending on both chelate and nucleophile. Thus, with t BuLi, an unprecedented addition to C5 of bipy, a regiochemistry not accessible for free bipy, was obtained, whereas coordinated phen underwent t BuLi addition to C2 and C4. Remarkably, when LiHBEt3 reacted with [Re(bipy)(CO)3 (PMe3 )]OTf, hydride addition to the 4 and 6 positions of bipy triggered an intermolecular cyclodimerization of two dearomatized pyridyl rings. In contrast, hydride addition to the phen analog resulted in partial reduction of one pyridine ring. The resulting neutral Re I products showed a varied reactivity with HOTf and with MeOTf to yield cationic complexes. These strategies rendered access to Re I complexes containing bipy‐ and phen‐derived chelates with several C(sp 3 ) centers. Abstract : Everything is possible with bipy and phen in the game: Post‐coordination functionalization of 2, 2′‐bipyridine (bipy) and 1, 10‐phenanthroline (phen) has been applied to the synthesis of {Re I (CO)3 } complexes containing C(sp 3 ) derivatives of the aromatic chelates. The additions of t BuLi and of LiHBEt3 to Re‐coordinated bipy and phen showed unprecedented site‐selectivity and triggered reaction pathways such as cyclodimerization or reduction.